Influence of the valve-seat gap on the dynamics of reed type valves - Moimás, Gabriel Biancolin [UNESP] (2020)
One of the main parts of refrigeration compressors is the automatic valve system used to control the suction and discharge processes. Experimental studies of these processes in the compressor environment are complex because the small size of the compressor. Thus, experimental analysis in enlarged valve models is useful for improving the understanding of the flow characteristics. This work consists of an experimental investigation into the fluid–structure interaction problem due to the flow acting on the valve surfaces in enlarged reed type valves, aimed at evaluating the influence of the valve-seat gap on the dynamic behavior of the valve. The instantaneous position of the valve was measured by using an optical sensor for flows with Reynolds number based in the orifice inlet parameters varying from about 2000 to 19,000. It was found that even a small valve-seat gap significantly influences the dynamic behavior of the valve. An abrupt increase in the amplitude of the valve displacement occurs in a narrow range of Reynolds number due to flutter. For lower stiffness valves, this phenomenon occurs for Reynolds numbers varying from about 6000 to 8000. For higher stiffness valves, it occurs for Reynolds numbers varying from about 2000 to 3000. When the valve is assembled without a gap, the amplitude increases monotonically, without the appearance of flutter. The article also presents how these results are useful to validate computational codes typically employed to investigate fluid–structure interaction problems in reed type valves, especially because the valve-seat gap is required in most computational codes.